Solidified soil with anti-cracking and anti-shrinkage functions and preparation method thereof

By adding specific components to the cured soil, cured soil with anti-cracking and shrinkage functions are prepared, which solves the problem that the cured soil is prone to cracks and shrinkage during maintenance and use, and significantly improves its strength and water stability, especially in summer construction.

CN119750973AActive Publication Date: 2025-04-04江苏省科佳设计集团股份有限公司 +1

Patent Information

Application Number
CN202411949973.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The solidified soil is prone to cracks and shrinkage during maintenance and use, which affects its strength and reliability, especially during summer construction.

Method used

By adding components such as blast furnace slag, calcium oxide, sodium silicate, hyperalgesic soil, sodium carbonate, γ-aminopropyltriethoxysilane, phase change material microcapsules and graphene oxide to the cured soil, cured soil with anti-cracking and anti-shrinkage functions are prepared. This method reduces the temperature gradient and moisture content changes of the solidified soil through the mechanism of temperature control, expansion, moisturizing and toughening, and reduces the occurrence of cracks and shrinkage.

Benefits of technology

It significantly improves the crack resistance and shrinkage resistance of the cured soil, reduces the total dry shrinkage coefficient and maximum temperature shrinkage coefficient, enhances the strength and water stability of the cured soil, and improves its application performance in summer construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses solidified soil with anti-cracking and anti-shrinkage functions and a preparation method of the solidified soil, and the solidified soil comprises a solidified material and soil, the raw materials of the high-temperature-resistant anti-freezing agent comprise the following components: 50-60 parts of blast furnace slag, 5-8 parts of calcium oxide, 15-20 parts of sodium silicate, 10-15 parts of metakaolin, 2-5 parts of sodium carbonate, 1-3 parts of gamma-aminopropyltriethoxysilane, 5-10 parts of phase change material microcapsules, 1-3 parts of graphene oxide, 10-15 parts of calcium sulfate, 3-5 parts of polyethylene glycol, 1-3 parts of polyvinyl alcohol, 2.4-4.8 parts of aluminum sulfate, 2-5 parts of sodium lignin sulfonate and 1.6-3.2 parts of titanium sulfate. The mass of the curing material is not less than 6% of that of soil. According to the solidified soil, the components in the raw materials are blended, so that the solidified soil is high in strength and good in water stability and has excellent anti-cracking and anti-shrinkage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of mud solidification, and in particular to solidified soil with anti-cracking and anti-shrinkage functions and a preparation method thereof. Background Art

[0002] Solidified soil is generally composed of finely divided granular soil particles and inorganic cementitious materials, which makes it easy to crack during maintenance and use. Especially during summer construction, cracks on the surface of solidified soil often occur, which affects the strength of solidified soil, reduces the reliability of solidified soil materials, and limits the application of solidified soil materials. The main reasons for the easy cracking and shrinkage of solidified soil materials are as follows: inorganic cementitious materials will react with water in the soil, resulting in a decrease in the moisture content of solidified soil and shrinkage cracks; in the initial stage of soil solidification, inorganic cementitious materials will release a lot of heat, resulting in the internal temperature of the soil higher than the surface temperature of the soil; in the later stage of solidification, the surface of solidified soil is affected by direct sunlight, especially during summer construction, the surface temperature of solidified soil is higher than the internal temperature, resulting in a temperature gradient inside and outside the solidified soil, resulting in temperature cracks; the surface of solidified soil is directly in contact with the air, resulting in a higher water loss rate on the surface of solidified soil than the internal water loss rate, and the surface temperature of solidified soil increases due to direct sunlight, which accelerates the water loss rate on the surface of solidified soil, promotes the shrinkage of the surface of solidified soil, while the internal shrinkage of solidified soil is slower, and there is a shrinkage difference between the surface and the inside of solidified soil, resulting in cracks in solidified soil. Therefore, the cracks and shrinkage of solidified soil are mainly affected by temperature and moisture content. The two complement each other and jointly promote the development of cracks in solidified soil.

[0003] Patent CN 115490497 A achieves the anti-cracking property of the solidified soil by adding polypropylene fibers to the solidifying agent. However, in order to achieve good anti-cracking property of the solidified soil, the fibers and the soil need to be fully mixed evenly, and it is difficult to fully mix the fibers and the soil with existing engineering machinery and equipment.

[0004] The patent application document with application number 202311855794.5 discloses a method for preparing a fiber-reinforced composite curing agent composed of carbide slag, desulfurized gypsum and glass fiber for reinforcing silt. The tensile and pull-out properties of the glass fiber itself are used to prevent the development of cracks. However, in order to achieve a good anti-cracking effect, how to evenly mix the glass fiber with the soil will be the main reason hindering the engineering application of this method.

[0005] Patent CN117003529B uses cement, desulfurization ash, carbide slag, fly ash, soil penetrant, high-performance water reducer and polyester fiber to solidify waste soil. It adopts the same idea as the above patent and achieves anti-cracking effect by adding polyester fiber. However, how to mix the fibers evenly is a practical problem that is difficult to solve during the construction process of this method.

[0006] Patent CN111116157B reduces the cracking of solidified soil by adding calcium sulfate and magnesium oxide to the curing agent, and the early expansion caused by the formation of calcium sulfate and the late expansion of magnesium oxide. However, this method has the following main problems: the soil is composed of granular bulk materials with rich internal pores. In order to achieve the anti-cracking effect, the expansion component content of the curing agent must correspond to the porosity of the soil. Too little will not have the anti-cracking effect, and too much will cause expansion and cracking. In addition, the expansion rate of the curing agent must match the contraction of the soil, otherwise the deformation mismatch will make it easier to form cracks.

[0007] As can be seen from the above, the existing technical means have not effectively solved the defect that the solidified soil is prone to cracking and shrinking. Therefore, there is still an urgent need for a solidification material and method that can better solve the problem that the solidified soil is prone to cracking and shrinking. Summary of the invention

[0008] Purpose of the invention: The first purpose of the present invention is to provide a solidified soil with anti-cracking and anti-shrinkage functions; the second purpose of the present invention is to provide a method for preparing the solidified soil.

[0009] Technical solution: The premixed early-strength fluidized solidified soil of the present invention comprises solidifying materials and soil. The solidifying materials are calculated by weight, and the raw materials include the following components: 50-60 parts of blast furnace slag, 5-8 parts of calcium oxide, 15-20 parts of sodium silicate, 10-15 parts of meta-old soil, 2-5 parts of sodium carbonate, 1-3 parts of γ-aminopropyltriethoxysilane, 5-10 parts of phase change material microcapsules, 1-3 parts of graphene oxide, 10-15 parts of calcium sulfate, 3-5 parts of polyethylene glycol, 1-3 parts of polyvinyl alcohol, 2.4-4.8 parts of aluminum sulfate, 2-5 parts of sodium lignin sulfonate, and 1.6-3.2 parts of titanium sulfate; the mass of the solidifying materials is not less than 6% of the mass of the soil;

[0010] The phase change material microcapsules include the following raw materials by weight: 8-12 parts of paraffin, 1-2 parts of hexamethylene diisocyanate, 1-2 parts of polyethylene glycol, 0.38-1.1 parts of polyvinyl alcohol, 0.01-0.02 parts of triethylamine, 2-8 parts of dichloromethane, and 25-30 parts of water.

[0011] In the phase change material microcapsule, paraffin is used as the phase change material and the other materials are used as the wall material, which has long-term stability in alkaline and humid environments.

[0012] Preferably, the mass of the solidifying material is 6-15% of the mass of the soil. For solidifying soil with higher requirements for strength and crack resistance, a high dosage can be selected, while for solidifying soil with lower requirements, a low dosage can be selected.

[0013] Preferably, the melting point of the paraffin wax is 25-40°C.

[0014] Preferably, the molecular weight of the polyethylene glycol is 2000-10000.

[0015] Preferably, the molecular weight of the polyvinyl alcohol is 17,000 to 30,000.

[0016] Preferably, the sodium silicate is a powder with a modulus of 1.

[0017] The method for preparing the stabilized soil with anti-cracking and anti-shrinkage functions of the present invention comprises the following steps:

[0018] (1) Weighing polyvinyl alcohol and adding it to water to dissolve to obtain a polyvinyl alcohol solution, spraying the polyvinyl alcohol solution on the soil to be solidified, and mixing and stirring to be uniform, wherein the moisture content of the soil after spraying the polyvinyl alcohol solution is 2 to 3% higher than the optimal moisture content, to obtain a mixed material A;

[0019] (2) Weigh γ-aminopropyltriethoxysilane, spray it evenly on material A, and mix well to obtain material B;

[0020] (3) Weigh blast furnace slag, kaolin, calcium sulfate, aluminum sulfate, titanium sulfate and sodium lignin sulfonate, add to material B and mix evenly to obtain material C;

[0021] (4) Weighing polyethylene glycol, phase change material microcapsules and graphene oxide, adding them to material C, mixing and stirring to obtain material D;

[0022] (5) Weigh calcium oxide, sodium silicate and sodium carbonate, add them to material D, mix and stir evenly to obtain the solidified soil with anti-cracking and anti-shrinkage functions.

[0023] The optimal moisture content described in step (1) is a basic material parameter of soil and can be obtained through geotechnical compaction test.

[0024] Preferably, the method for preparing the phase change material microcapsules comprises the following steps:

[0025] (1) adding polyvinyl alcohol to water to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution;

[0026] (2) heating the paraffin wax to a temperature above the melting point to completely melt it, then slowly dropping the paraffin wax into the polyvinyl alcohol solution, and using ultrasonic dispersion to form a uniform paraffin wax emulsion;

[0027] (3) pouring hexamethylene diisocyanate into dichloromethane and mixing until completely dissolved to form a hexamethylene diisocyanate solution;

[0028] (4) pouring polyethylene glycol into the hexamethylene diisocyanate solution and stirring to mix them evenly;

[0029] (5) adding the solution in step (4) to the paraffin emulsion prepared in step (2) and stirring continuously to obtain a uniform mixed solution;

[0030] (6) adding triethylamine dropwise to the mixed solution obtained in step (5) and stirring the mixture continuously, wherein the temperature of the mixed solution is 40 to 50° C., the stirring time is 2 to 3 hours, and the mixture is cooled to room temperature after the reaction is completed;

[0031] (7) Separating microcapsules from the solution obtained in step (6), and drying the separated microcapsules to obtain microcapsules with phase change function.

[0032] In step (6), paraffin is used as the core material and is coated with a polyurethane shell formed by the cross-linking reaction of hexamethylene diisocyanate and polyethylene glycol. The shell is evenly coated on the surface of the paraffin emulsion droplets, thereby forming a stable microcapsule structure to form microcapsules.

[0033] Preferably, in step (7), the separation of microcapsules is: placing the solution into a centrifuge at a speed of 3000 to 5000 rpm for 10 to 20 minutes to separate the microcapsules.

[0034] Preferably, in step (7), the drying temperature is 40-50°C.

[0035] Invention mechanism:

[0036] This patent achieves the purpose of anti-cracking and shrinkage through temperature control, expansion, moisture retention and toughening. The main mechanism is as follows:

[0037] (1) The shrinkage and cracking of the solidified soil are most likely to occur during the curing stage. When the solidified material meets water, it will be hydrated and release a large amount of heat. This heat is absorbed by the phase change microcapsules, so that the temperature of the solidified soil remains relatively constant. In addition, during construction in summer, the surface of the solidified soil is exposed to direct sunlight, and the surface temperature of the solidified soil rises rapidly, resulting in inconsistent temperatures between the surface and the interior of the solidified soil. In the present invention, the phase change microcapsules can store a portion of the heat of the sunlight, and the graphene oxide can enhance the thermal conductivity of the solidified soil, and the heat on the surface of the solidified soil can be transferred to the interior of the solidified soil, thereby reducing the temperature gradient of the solidified soil and reducing the cracking of the solidified soil caused by the temperature gradient. In addition, due to the addition of the phase change microcapsules, the temperature of the soil body remains relatively stable. Combined with the polyethylene glycol with water retention function, the loss of water on the surface of the solidified soil caused by sunlight exposure can be significantly reduced, and the probability of cracks on the surface can be reduced.

[0038] (2) Blast furnace slag and relatively old soil undergo inorganic polymerization under the action of sodium silicate, calcium oxide and sodium carbonate. In the process of generating geopolymers, the free water in the soil is consumed, resulting in a decrease in the moisture content of the soil. The decrease in moisture content will also cause the soil to shrink and crack. To compensate for this shrinkage, the sulfate ions in the curing agent will react with calcium oxide, blast furnace slag and sodium silicate to form hydrated products such as calcium aluminate, resulting in volume expansion, which compensates for the shrinkage caused by the decrease in moisture content and reduces the risk of shrinkage and cracking of the cured soil.

[0039] (3) After hydration, the solidifying material ionizes aluminum ions and titanium ions, which can form coordination bonds with the hydroxyl groups in polyvinyl alcohol, so that the polymers are cross-linked, forming a spatial network structure in the soil skeleton, forming a soil reinforcement effect similar to fiber, which can effectively disperse stress, increase the tensile strength of the solidified soil, and prevent the early cracking of the solidified soil. The amino group at one end of the γ-aminopropyltriethoxysilane molecule can react with the hydroxyl group in polyethylene glycol, while the siloxy group at the other end can bond with the silicate and aluminate in the geopolymer, forming a bridge between polyethylene glycol and the geopolymer, prompting the geopolymer matrix to form a spatial cross-linked network along the polyvinyl alcohol molecular chain attached to the surface of the soil particles, so that the fiber reinforcement effect formed after the cross-linking of polyvinyl alcohol is further enhanced, which can play a good role in limiting the cracking of the solidified soil in the middle and late stages.

[0040] In summary, based on the synergistic effects of temperature control, moisture retention, expansion compensation, and spatial cross-linked skeleton construction in the present technical solution, the curing agent can be made to have the function of resisting cracking and preventing shrinkage.

[0041] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The solidified soil has high strength, good water stability, and excellent anti-cracking and anti-shrinkage properties through the preparation of various components in the raw materials; (2) The total shrinkage coefficient of the solidified soil can reach 0.24‰, and the maximum temperature shrinkage coefficient is 0.296‰; (3) The preparation method is simple. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below in conjunction with embodiments.

[0043] Examples 1 to 3

[0044] A solidified soil with the function of resisting cracking and preventing shrinkage comprises a solidifying material and soil, wherein the raw material proportion of the solidifying material is as shown in Table 1.

[0045] Table 1 Raw material ratio of curing materials of Examples 1 to 3 (parts by mass)

[0046]

[0047]

[0048] The raw materials of the phase change material microcapsules include the following components by weight: 8-12 parts of paraffin, 1-2 parts of hexamethylene diisocyanate, 1-2 parts of polyethylene glycol, 0.38-1.1 parts of polyvinyl alcohol, 0.01-0.02 parts of triethylamine, 2-8 parts of dichloromethane and 25-30 parts of water. The raw material ratios of the phase change material microcapsules of Examples 1-3 are shown in Table 2.

[0049] Table 2 Raw material ratios of phase change material microcapsules of Examples 1 to 3 (parts by mass)

[0050]

[0051] The preparation method of phase change material microcapsules is as follows:

[0052] (1) adding polyvinyl alcohol to water to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution;

[0053] (2) heating the paraffin wax to above the melting point to completely melt it, then slowly dropping it into the polyvinyl alcohol solution, and using ultrasonic dispersion to form a uniform paraffin wax emulsion;

[0054] (3) pouring hexamethylene diisocyanate into dichloromethane and mixing until it is completely dissolved to form a hexamethylene diisocyanate solution;

[0055] (4) pouring polyethylene glycol into the hexamethylene diisocyanate solution and stirring to mix them evenly;

[0056] (5) adding the solution in step (4) to the paraffin emulsion and stirring continuously to obtain a uniform mixed solution;

[0057] (6) slowly adding triethylamine dropwise to the mixed solution obtained in step (5) while stirring continuously for 2 hours at a stirring speed of 1000 rpm and a temperature of 40° C. to 50° C., and cooling to room temperature after the reaction is completed;

[0058] (7) The solution obtained in the previous step is placed in a centrifuge at a speed of 4000 rpm for 15 min to separate microcapsules. The separated microcapsules are placed in an oven at 40° C.-50° C. to dry, thereby preparing microcapsules with phase change function.

[0059] The method for preparing the solidified soil comprises the following steps:

[0060] (1) Weigh polyvinyl alcohol according to the mass fraction in Table 1, dissolve it in water to prepare a polyvinyl alcohol solution, spray the polyvinyl alcohol solution on the soil to be solidified (the soil to be solidified is low liquid limit silty clay with an optimal moisture content of 15.3%, the amount of solidifying material is 8% of the soil mass, and the moisture content of the solidified soil after spraying the polyvinyl alcohol solution is 17.3%), and mix and stir evenly to obtain a mixed material A;

[0061] (2) Weighing γ-aminopropyltriethoxysilane according to the mass fraction, and spraying the γ-aminopropyltriethoxysilane evenly on the material A, and mixing evenly to obtain the material B;

[0062] (3) Weigh the following raw materials according to mass fraction: blast furnace slag, kaolin, calcium sulfate, aluminum sulfate, titanium sulfate, sodium lignin sulfonate, add them to material B, mix and stir, and obtain material C;

[0063] (4) Weighing polyethylene glycol, phase change material microcapsules, and graphene oxide according to mass fractions, adding them to material C, and mixing and stirring to obtain material D;

[0064] (5) Finally, the following raw materials are weighed according to their mass fractions: calcium oxide, sodium silicate, and sodium carbonate, and added to material D, and mixed and stirred evenly to obtain the solidified soil having the function of resisting cracking and shrinkage.

[0065] The solidified soil prepared in Examples 1 to 3 was poured into a three-petal saturator to prepare a sample with a diameter of (50 mm) × height of (50 mm) and a compaction degree of 97%. The sample was tested in accordance with the "Testing Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering (JTG E51-2009)". The test results are shown in Table 3:

[0066] Table 3 Experimental results of Examples 1 to 3

[0067]

[0068]

[0069] The test results show that the curing agent prepared with the three mix ratios given in the embodiment has a good curing effect on soft soil, and the unconfined compressive strength can reach up to 4.07MPa after normal curing for 7 days; the three-dimensional cross-linked structure generated by the internal reaction of the sample improves the toughness of the sample. After 5 freeze-thaw cycles, the sample has a complete appearance, no cracks appear on the surface of the sample, and the strength loss rate of the sample is only 2% to 3%. The total shrinkage coefficient and maximum temperature shrinkage coefficient of the sample are also very small, indicating that the sample has good anti-cracking and anti-shrinkage functions.

[0070] Comparative Example 1

[0071] The same as Example 3, except that, by weight, the raw materials of this comparative example include: 60 parts of blast furnace slag, 8 parts of calcium oxide, 20 parts of sodium silicate, 15 parts of meta-kaolin and 5 parts of sodium carbonate. Preparation method: Add blast furnace slag and meta-kaolin to low liquid limit clay and mix and stir evenly to obtain material C, then add calcium oxide, sodium silicate and sodium carbonate to material C, mix and stir evenly to obtain the material described in comparative example 1.

[0072] The samples were tested according to the “Test Procedure for Materials Stabilized by Inorganic Binders for Highway Engineering (JTG E51—2009)”. The test results are shown in Table 4.

[0073] Table 4 Comparative Example Test Results

[0074]

[0075] The test results show that: since only the components of the gelling material are provided in Comparative Example 1, the performance of the sample is greatly reduced, especially after the freeze-thaw cycle, the sample breaks and cannot achieve the anti-cracking and anti-shrinkage functions.

[0076] Comparative Example 2

[0077] The same as Example 3, except that, by weight, the raw materials of this comparative example include: 60 parts of blast furnace slag, 8 parts of calcium oxide, 20 parts of sodium silicate, 15 parts of metakaolin, 5 parts of sodium carbonate, 15 parts of calcium sulfate, 4.8 parts of aluminum sulfate and 3.2 parts of titanium sulfate.

[0078] Preparation method: Weigh the following raw materials according to their mass fractions: blast furnace slag, kaolin, calcium sulfate, aluminum sulfate, and titanium sulfate, add them to low liquid limit clay and mix and stir, and mix and stir to obtain material C; then, weigh the following raw materials according to their mass fractions: calcium oxide, sodium silicate, and sodium carbonate, add them to material C, mix and stir evenly, and obtain the material described in Comparative Example 2.

[0079] The samples were tested according to the “Test Procedure for Materials Stabilized by Inorganic Binders for Highway Engineering (JTG E51—2009)”. The test results are shown in Table 4.

[0080] The test results show that although the performance of Comparative Example 2 is improved compared with that of Comparative Example 1, the various properties of Comparative Example 2 are still greatly reduced compared with those of the embodiment because a spatial cross-linked structure cannot be well formed inside the sample. It breaks after 5 freeze-thaw cycles and cannot achieve the functions of anti-cracking and anti-shrinkage.

[0081] Comparative Example 3

[0082] The same as Example 3, except that, by mass, the raw materials of this comparative example include: 60 parts of blast furnace slag, 8 parts of calcium oxide, 20 parts of sodium silicate, 15 parts of metakaolin, 5 parts of sodium carbonate, 15 parts of calcium sulfate, 5 parts of polyethylene glycol, 3 parts of polyvinyl alcohol, 4.8 parts of aluminum sulfate, 5 parts of sodium lignin sulfonate and 3.2 parts of titanium sulfate.

[0083] Preparation method: Weigh polyvinyl alcohol according to mass fraction to prepare polyvinyl alcohol solution, spray the polyvinyl alcohol solution on the soil to be solidified, mix and stir evenly to obtain mixed material A. Weigh the following raw materials according to mass fraction: blast furnace slag, kaolin, calcium sulfate, aluminum sulfate, titanium sulfate, sodium lignin sulfonate, add to material A, mix and stir, and obtain material C; weigh polyethylene glycol according to mass fraction, add to material C, mix and stir to obtain material D; finally, weigh the following raw materials according to mass fraction: calcium oxide, sodium silicate, sodium carbonate, add to material D, mix and stir evenly, and obtain the material described in comparative example 3.

[0084] The samples were tested according to the “Test Procedure for Materials Stabilized by Inorganic Binders for Highway Engineering (JTG E51—2009)”. The test results are shown in Table 4.

[0085] The test results show that due to the lack of γ-aminopropyltriethoxysilane, phase change material microcapsules and graphene oxide, the reinforcing effect of the spatial cross-linked structure on the soil skeleton is weakened, and the influence of temperature on the sample is increased. Therefore, although the sample in Comparative Example 3 did not break, cracks existed on the surface of the sample, and after 5 freeze-thaw cycles, the strength was greatly reduced. In addition, the shrinkage resistance of the sample is still far behind that of Example 3.

[0086] Comparative Example 4

[0087] The same as Example 3, except that, by mass, the raw materials of this comparative example include: 60 parts of blast furnace slag, 8 parts of calcium oxide, 20 parts of sodium silicate, 15 parts of metakaolin, 5 parts of sodium carbonate, 3 parts of γ-aminopropyltriethoxysilane, 15 parts of calcium sulfate, 5 parts of polyethylene glycol, 3 parts of polyvinyl alcohol, 4.8 parts of aluminum sulfate, 5 parts of sodium lignin sulfonate and 3.2 parts of titanium sulfate.

[0088] Preparation method: Weigh polyvinyl alcohol according to mass fraction to prepare polyvinyl alcohol solution, spray the polyvinyl alcohol solution on the soil to be solidified, and mix and stir evenly to obtain mixed material A. Subsequently, weigh γ-aminopropyl triethoxysilane according to mass fraction, spray γ-aminopropyl triethoxysilane evenly on material A, and mix evenly to obtain material B. Weigh the following raw materials according to mass fraction: blast furnace slag, metakaolin, calcium sulfate, aluminum sulfate, titanium sulfate, sodium lignin sulfonate, add to material B, mix and stir, and obtain material C; weigh polyethylene glycol according to mass fraction, add to material C, mix and stir to obtain material D; finally, weigh the following raw materials according to mass fraction: calcium oxide, sodium silicate, sodium carbonate, add to material D, mix and stir evenly, and obtain the material of comparative example 4.

[0089] The samples were tested according to the “Test Procedure for Materials Stabilized by Inorganic Binders for Highway Engineering (JTG E51—2009)”. The test results are shown in Table 4.

[0090] The test results show that due to the lack of phase change material microcapsules and graphene oxide, the temperature sensitivity of the sample increases. After 5 dry-wet cycles, the sample in Comparative Example 4 has microcracks on the surface of the sample, and the strength loss rate of the sample is 12.6%, which is higher than the strength loss rate in Example 3. In addition, due to the microcracks on the surface of the sample, the integrity of the sample is reduced, resulting in a decrease in the shrinkage resistance of the sample compared with Example 3.

[0091] Comparative Example 5

[0092] The same as Example 3, except that, by mass, the raw materials of this comparative example include: 60 parts of blast furnace slag, 8 parts of calcium oxide, 20 parts of sodium silicate, 15 parts of metakaolin, 5 parts of sodium carbonate, 10 parts of phase change material microcapsules, 3 parts of graphene oxide, 15 parts of calcium sulfate, 5 parts of polyethylene glycol, 4.8 parts of aluminum sulfate, 5 parts of sodium lignin sulfonate and 3.2 parts of titanium sulfate.

[0093] Preparation method: Weigh the following raw materials according to their mass fractions: blast furnace slag, metakaolin, calcium sulfate, aluminum sulfate, titanium sulfate, sodium lignin sulfonate, add them to low liquid limit clay and mix and stir to obtain material C; weigh polyethylene glycol, phase change material microcapsules, and graphene oxide according to their mass fractions, add them to material C, mix and stir to obtain material D; finally, weigh the following raw materials according to their mass fractions: calcium oxide, sodium silicate, and sodium carbonate, add them to material D, mix and stir evenly, and obtain the material described in Comparative Example 5.

[0094] According to the "Highway Geotechnical Test Code (JTG 3430-2020)", the compressive strength of the samples was measured, and the test results are shown in Table 4.

[0095] The test results show that due to the lack of polyvinyl alcohol and γ-aminopropyltriethoxysilane, the curing material cannot form a spatial cross-linked network in the soil. After 5 dry-wet cycles, the sample in Comparative Example 5 has microcracks on the surface of the sample, and the strength loss rate of the sample is 21.3%, which is significantly higher than the strength loss rate in Example 3. In addition, the shrinkage resistance of the sample is also greatly reduced compared with the examples.

[0096] Comparative Example 6

[0097] The same as Example 3, except that, by mass, the raw materials of this comparative example include: 3 parts of γ-aminopropyltriethoxysilane, 10 parts of phase change material microcapsules, 3 parts of graphene oxide, 15 parts of calcium sulfate, 5 parts of polyethylene glycol, 3 parts of polyvinyl alcohol, 4.8 parts of aluminum sulfate, 5 parts of sodium lignin sulfonate and 3.2 parts of titanium sulfate.

[0098] Preparation method: Weigh polyvinyl alcohol according to mass fraction to prepare polyvinyl alcohol solution, spray the polyvinyl alcohol solution on the soil to be solidified, and mix and stir evenly to obtain mixed material A. Subsequently, weigh γ-aminopropyltriethoxysilane according to mass fraction, spray γ-aminopropyltriethoxysilane evenly on material A, and stir evenly to obtain material B. Weigh the following raw materials according to mass fraction: calcium sulfate, aluminum sulfate, titanium sulfate, sodium lignin sulfonate, add them to material B and mix and stir to obtain material C; weigh polyethylene glycol, phase change material microcapsules, and graphene oxide according to mass fractions, and add them to material C to obtain the material described in comparative example 6.

[0099] According to the "Highway Geotechnical Test Code (JTG 3430-2020)", the compressive strength of the samples was measured, and the test results are shown in Table 4.

[0100] The test results show that due to the lack of gelling components in the solidifying material and the lack of the reinforcement effect of the spatial cross-linking structure on the soil skeleton, the sample in Comparative Example 6 broke directly after 5 dry-wet cycles. In addition, the other properties of the sample were greatly reduced compared with those of Example 3, and the anti-cracking and anti-shrinkage effects could not be achieved.

Claims

1. A solidified soil with anti-cracking and anti-shrinkage functions, characterized in that: Including solidifying materials and soil. The solidifying materials are calculated by weight, and the raw materials include the following components: 50-60 parts of blast furnace slag, 5-8 parts of calcium oxide, 15-20 parts of sodium silicate, 10-15 parts of kaolin, 2-5 parts of sodium carbonate, 1-3 parts of γ-aminopropyltriethoxysilane, 5-10 parts of phase change material microcapsules, 1-3 parts of graphene oxide, 10-15 parts of calcium sulfate, 3-5 parts of polyethylene glycol, 1-3 parts of polyvinyl alcohol, 2.4-4.8 parts of aluminum sulfate, 2-5 parts of sodium lignin sulfonate, and 1.6-3.2 parts of titanium sulfate; the mass of the solidifying materials shall not be less than 6% of the mass of the soil; The phase change material microcapsules include the following raw materials by weight: 8-12 parts of paraffin, 1-2 parts of hexamethylene diisocyanate, 1-2 parts of polyethylene glycol, 0.38-1.1 parts of polyvinyl alcohol, 0.01-0.02 parts of triethylamine, 2-8 parts of dichloromethane, and 25-30 parts of water.

2. The stabilized soil with anti-cracking and anti-shrinkage function according to claim 1, characterized in that: The mass of the solidified material is 6-15% of the mass of the soil.

3. The stabilized soil with anti-cracking and anti-shrinkage function according to claim 1, characterized in that: The melting point of the paraffin wax is 25-40°C.

4. The stabilized soil with anti-cracking and anti-shrinkage function according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 2000-10000.

5. The stabilized soil with anti-cracking and anti-shrinkage function according to claim 1, characterized in that: The molecular weight of the polyvinyl alcohol is 17000-30000.

6. The stabilized soil with anti-cracking and anti-shrinkage function according to claim 1, characterized in that: The sodium silicate is a powder with a modulus of 1.

7. A method for preparing the stabilized soil with anti-cracking and anti-shrinkage functions according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weighing polyvinyl alcohol, adding it to water to dissolve it to obtain a polyvinyl alcohol solution, spraying the polyvinyl alcohol solution on the soil to be solidified, and mixing and stirring it evenly, wherein the moisture content of the soil after spraying the polyvinyl alcohol solution is 2 to 3% higher than the optimal moisture content, thereby obtaining a mixed material A; (2) Weighing γ-aminopropyltriethoxysilane and spraying it evenly on material A, mixing evenly, to obtain material B; (3) Weigh blast furnace slag, kaolin, calcium sulfate, aluminum sulfate, titanium sulfate and sodium lignin sulfonate, add to material B and mix evenly to obtain material C; (4) Weighing polyethylene glycol, phase change material microcapsules and graphene oxide, adding them to material C, mixing and stirring to obtain material D; (5) Weigh calcium oxide, sodium silicate and sodium carbonate, add them to material D, mix and stir evenly to obtain the solidified soil with anti-cracking and anti-shrinkage functions.

8. The method for preparing the stabilized soil with anti-cracking and anti-shrinkage functions according to claim 7, characterized in that: The preparation method of the phase change material microcapsule comprises the following steps: (1) adding polyvinyl alcohol to water to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution; (2) heating the paraffin wax to a temperature above the melting point to completely melt it, then dropping the paraffin wax into the polyvinyl alcohol solution, and using ultrasonic dispersion to form a uniform paraffin wax emulsion; (3) pouring hexamethylene diisocyanate into dichloromethane and mixing until completely dissolved to form a hexamethylene diisocyanate solution; (4) pouring polyethylene glycol into the hexamethylene diisocyanate solution and stirring to mix them evenly; (5) adding the solution in step (4) to the paraffin emulsion prepared in step (2) and stirring continuously to obtain a uniform mixed solution; (6) adding triethylamine dropwise to the mixed solution obtained in step (5) while stirring continuously, the temperature of the mixed solution is 40 to 50° C., the stirring time is 2 to 3 hours, and after the reaction is completed, cooling to room temperature; (7) Separating microcapsules from the solution obtained in step (6), and drying the separated microcapsules to obtain microcapsules with phase change function.

9. The method for preparing stabilized soil with anti-cracking and anti-shrinkage functions according to claim 8, wherein in step (7), the separation of microcapsules is: placing the solution into a centrifuge at a speed of 3000 to 5000 rpm for 10 to 20 minutes to separate the microcapsules.

10. The method for preparing stabilized soil with anti-cracking and anti-shrinkage functions according to claim 8, wherein in step (7), the drying temperature is 40-50°C.

Citation Information

Patent Citations

  • A method for preparing and applying silt-stabilized soil in coastal areas

    CN111116157B

  • Preparation method of fiber reinforced composite curing agent for reinforcing sludge

    CN117800694A

  • Porous geopolymer-based phase-change energy storage material

    CN103641433A

  • Tough geopolymer curing material for improving performance of silt soft soil and preparation method of tough geopolymer curing material

    CN116425461A

  • Additive for rapidly improving grouting strength of solidified soil and preparation method of additive

    CN116854399A

Cited By

  • Building waste environment-friendly water stabilizing material as well as preparation method and application thereof

    CN120647211A

  • Carbide slag-based low-carbon gel material and preparation method thereof

    CN121107767A